Endometrial claudin-4 and leukemia inhibitory factor are associated with assisted reproduction outcome - Motta Eduardo LA; Smith Gary D; Silva Ismael DCG; Serafini Paulo C; Rocha André M; Baracat Edmund C (BMC, 2009)
Abstract Background Claudin-4 (CLDN4) is one of several proteins that act as molecular mediators of embryo implantation. Recently, we examined immunolabeling of leukemia inhibitory factor (LIF) in the endometrial tissue of 52 IVF patients, and found that LIF staining intensity was strongly correlated with successful pregnancy initiation. In the same set of patients, we have now examined endometrial CLDN4 expression, to see how expression intensity may vary with LIF. We examined CLDN4 in the luteal phase of the menstrual cycle, immediately preceding IVF treatment. Our aim was to compare expression of LIF and CLDN4 in the luteal phase, and document these patterns as putative biomarkers for pregnancy. Methods Endometrial tissue was collected from women undergoing IVF. Endometrial biopsies were obtained during the luteal phase preceding IVF, and were then used for tissue microarray (TMA) immunolabeling of CLDN4. Previously published LIF expression data were then combined with CLDN4 expression data, to determine CLDN4/LIF expression patterns. Associations between successful pregnancy after IVF and combined CLDN4/LIF expression patterns were evaluated. Results Four patterns of immunolabeling were observed in the endometrial samples: 16% showed weak CLDN4 and strong LIF (CLDN4-/LIF+); 20% showed strong CLDN4 and strong LIF (LIF+/CLDN4+); 28% showed strong CLDN4 and weak LIF (CLDN4+/LIF-); and 36% showed weak CLDN4 and weak LIF (CLDN4-/LIF-). Successful implantation after IVF was associated with CLDN4-/LIF+(p = 0.003). Patients showing this endometrial CLDN4-/LIF+ immunolabeling were also 6 times more likely to achieve pregnancy than patients with endometrial CLDN4+/LIF- immunolabeling (p = 0.007). Conclusion The combined immunolabeling expression of CLDN4-/LIF+ in endometrial tissue is a potential biomarker for predicting successful pregnancy in IVF candidates.